Thiosulfate as the electron acceptor in Sulfur Bioconversion-Associated Process (SBAP) for sewage treatment. (15th October 2019) - Qian, Jin; Zhang, Mingkuan; Jing, Ran; Bai, Linqin; Zhou, Bo; Zhao, Mingjun; Pei, Xiangjun; Wei, Li; Chen, Guang-Hao
Abstract: The s ulfur b ioconversion-a ssociated p rocesses (SBAP) for sewage treatment have been extensively reported so far. In this study, biological thiosulfate reduction (BTR)-driven biotechnology for high rate sulfidogenesis and organic removal was explored to further close the gap of our knowledge on the sulfur cycle-based sewage treatment bioprocess. With thiosulfate as the electron acceptor, the sulfidogenic rate in the UASB rector is 105.6 mg S/L/h with the sludge yield of only 0.044 g MLVSS/g CODsubstrate . Thus providing sufficient electron donors or chemical sources (i.e. HS − ) for the downstream autotrophic denitrification or for the cost-effective heavy metal precipitation. Thiosulfate disproportionation was not observed in BTR reactor. High-throughput pyrosequencing analysis reveals that Desulfobulbus and Desulfomicrobium are the predominant thiosulfate-reducing genera and the thiosulfate disproportionation-bacteria were at much lower genus level. The specific thiosulfate-reducer i.e. Dethiosulfatibacter which could utilize thiosulfate but not sulfate as the electron acceptor was also identified. Batch testing results indicate that the sulfidogenic activity on thiosulfate was 1.5 times that on sulfate. The optimal pH for BTR activity was between 7.0 and 8.0, a typical pH range of the municipal sewage. Thiosulfate can be efficiently recovered in the sulfide-driven denitritation reactor enriched with abundant sulfide-oxidizing genera (mainly including Thiobacillus and Sulfurimonas ). Finally, a conceptual model of the sulfur cycle based on the biotransformation between thiosulfate and sulfide was established, offering new insights into the sustainable SBAP with sludge minimization. Graphical abstract: Image 1 Highlights: S2 O3 2− as the electron acceptor in sulfur bioconversion-associated treatment process. High sulfidogenic capacity and low sludge yield could be achieved in S2 O3 2− reduction. S2 O3 2− reduction can be applied for both municipal and industrial wastewater treatment. Optimal pH for S2 O3 2− reduction is in the typical pH range of municipal sewage. A new sulfur cycle of S2 O3 2− ↔ HS − for sustainable sewage treatment was proposed.